2022
DOI: 10.1002/berj.3835
|View full text |Cite
|
Sign up to set email alerts
|

Social violence and the trivialising effects of youth in school bullying: Extended listening to South Australian young people on bullying and violence

Abstract: School bullying attracts significant research and resources globally, yet critical questions are being raised about the long-term impact of these efforts. There is a disconnect between young people's perspectives and the long-established psychology-based technical definitions of school bullying dominating practice and policy in Australia. This dominant paradigm has recently been described as the first paradigm of school bullying. In contrast, this paper explores the potential for reorienting school bullying re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…Tal como señalan Rey & Ortega (2007), aunque la violencia escolar más estudiada sea el acoso entre iguales, dentro de las escuelas los niños y jóvenes pueden verse implicados en otros tipos de violencia que también deben ser abordadas. Lohmeyer (2022), señala la importancia de priorizar los estudios sobre el acoso escolar, la exclusión de los jóvenes y su efecto en el conocimiento propio de los jóvenes, es decir dirigir la investigación sobre el acoso escolar hacia las preocupaciones de los jóvenes, más que en las definiciones de los adultos, enfatizar en el estudio de los elementos sociales, culturales y filosóficos del acoso escolar, bajo un enfoque más amplio, visto como violencia social el cual es un concepto que integra múltiples elementos.…”
Section: Desarrollo Antecedentes Del Estudio De La Violencia Escolar ...unclassified
“…Tal como señalan Rey & Ortega (2007), aunque la violencia escolar más estudiada sea el acoso entre iguales, dentro de las escuelas los niños y jóvenes pueden verse implicados en otros tipos de violencia que también deben ser abordadas. Lohmeyer (2022), señala la importancia de priorizar los estudios sobre el acoso escolar, la exclusión de los jóvenes y su efecto en el conocimiento propio de los jóvenes, es decir dirigir la investigación sobre el acoso escolar hacia las preocupaciones de los jóvenes, más que en las definiciones de los adultos, enfatizar en el estudio de los elementos sociales, culturales y filosóficos del acoso escolar, bajo un enfoque más amplio, visto como violencia social el cual es un concepto que integra múltiples elementos.…”
Section: Desarrollo Antecedentes Del Estudio De La Violencia Escolar ...unclassified
“…Bullying-a power domination behaviour by an individual or group to intentionally harm others either physically or emotionally over a period-is a social problem that is affecting children in all parts of the world [1][2][3][4][5][6][7][8][9]. Globally, almost one in three students (32%) are bullied by their peers at least once every month [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a strong association between school bullying victimisation and adverse health risks of mental, psychosocial, and behavioural problems as well as later life performance [7,8]. Bullying, as a violent and oppressive behaviour, causes harm, and, therefore, provides a powerful moral imperative for particular attention within social work education and intervention [9].…”
Section: Introductionmentioning
confidence: 99%